2008
DOI: 10.1177/154193120805200455
|View full text |Cite
|
Sign up to set email alerts
|

Multi-method Approach to Team Situation Awareness

Abstract: In this paper, we present our definition and multi-method approach to assess team SA, followed by an application of the measurement approach in a simulated air combat environment. In the simulation, team SA is measured using Situation Awareness Global Assessment Technique (SAGAT) on the elements related to own and teammate's responsibilities, confidence level on the accuracy of SAGAT responses, and awareness of teammate's workload and SA levels. The interrelationships between various measures of team SA, and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Nevertheless, studies from both laboratory and field have shown that SA is closely related to performance (Sulistyawati, Chui, &Wickens, 2008;Durso, 1998;Farley, Hansman, Amonlirdviman, &Endsley, 2000). It is generally accepted that good SA can be viewed as a factor that will increase the probability of good performance but cannot necessarily guarantee it (Endsley, 1995b shown to be essentially independent constructs (Endsley, 1993;Durso, 1998;Wickens, 2008).…”
Section: Situation Awareness (Sa) In Team Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, studies from both laboratory and field have shown that SA is closely related to performance (Sulistyawati, Chui, &Wickens, 2008;Durso, 1998;Farley, Hansman, Amonlirdviman, &Endsley, 2000). It is generally accepted that good SA can be viewed as a factor that will increase the probability of good performance but cannot necessarily guarantee it (Endsley, 1995b shown to be essentially independent constructs (Endsley, 1993;Durso, 1998;Wickens, 2008).…”
Section: Situation Awareness (Sa) In Team Settingsmentioning
confidence: 99%
“…Currently most researchers still choose measurements that were initially developed for measuring individual SA and adapt them to team settings. For example, in a simulated air combat environment, SAGAT was employed to probe aspects in the responsibilities of oneself and other team members (Sulistyawati et al, 2008). Similarly, in evaluating TSA, a SAGAT-like questionnaire was presented every 2 minutes during the 10-minute trial and the subjects answered questions regarding their own cognitive states and beliefs on the other team members' SA, beliefs in the other team members' belief on their own SA (Nonose, 2010).…”
Section: Situation Awareness (Sa) In Team Settingsmentioning
confidence: 99%